The Use of Geographic Information Systems (GIS) in Measuring the Accessibility to Educational Services in the Driouch province: A Geographical Approach for Planning - El-Kallouchi, Mohamed; Bouguelba, Ismail (Journal of Humanities & Social Sciences, 2025)
Education is considered the cornerstone of development and progress in any country, as achieving economic and human development becomes impossible without a strong focus on education, improving its quality, enhancing its appeal, and prioritizing it in national policies. Education has always been, and remains, of great importance for both developed countries and those on the path to growth. In this context, this study aims to highlight the educational challenges in the Driouch province, located in northeastern Morocco, by examining the evolution of student numbers, analyzing the spatial distribution of educational institutions, and assessing access to education using Geographic Information Systems (GIS). The study relied on field surveys and interviews with local residents and adopted a descriptive-analytical approach, integrating cartographic work for spatial analysis to provide a comprehensive examination of the data. Based on this, the study reached several conclusions, including: a decline in student numbers in Driouch due to school dropout, an uneven spatial distribution of educational institutions that exacerbates the education crisis, and that access to educational services remains very limited, especially for secondary education.To overcome the challenges related to the education sector in our field and ensure equity in access to these services, we propose a set of recommendations, including the construction of more educational institutions, particularly high schools, providing favorable conditions for schooling, revising the current school map, and universalizing preschool education, among others.
Keywords: Education; Planning and Social Development; Human Development; Driouch Province; Geographic Information Systems